1996
DOI: 10.3171/jns.1996.84.5.0742
|View full text |Cite
|
Sign up to set email alerts
|

Central neurocytoma: proliferative potential and biological behavior

Abstract: The authors analyzed 13 central neurocytomas diagnosed at Seoul National University Hospital between January 1982 and December 1993 to clarify the proliferative potential and biological behavior of these tumors. The tumor was confined to the lateral and third ventricles in 12 cases and in one case extended from the posterior thalamus to the body and trigone area of the lateral ventricle. In all 13 cases, typical clinical and radiological findings were observed, and histological diagnosis was performed via cran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 22 publications
5
53
0
Order By: Relevance
“…Limited data reported previously showed that central neurocytomas have low proliferative potential [3,43,44]. However, anaplasia has been demonstrated in recent literatures.…”
Section: Anaplasia Proliferative Potential and Biological Behaviormentioning
confidence: 94%
See 2 more Smart Citations
“…Limited data reported previously showed that central neurocytomas have low proliferative potential [3,43,44]. However, anaplasia has been demonstrated in recent literatures.…”
Section: Anaplasia Proliferative Potential and Biological Behaviormentioning
confidence: 94%
“…This report resulted in increased recognition of central neurocytomas and a number of case reports and series have been published since [1,2,3,36,39]. Despite their increased recognition, central neurocytomas remain rare neoplasms of the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,8,10,19) Standard initial treatment for central neurocytomas is a total resection whenever possible. 1,2,8,16,17,19,27) Histological and immunohistochemical examinations are necessary to establish the diagnosis differentially from oligodendroglioma or ependymoma. 3,8,9,13,15,19,22,29) The prognosis is usually favorable after gross total resection.…”
Section: Introductionmentioning
confidence: 99%
“…However, Tumors with indices greater than 2%, as in one series in which they were found to be 3% , are referred to as "atypical neurocytomas" and associated with a significantly shorter recurrence-free interval (53,56,57). …”
Section: Proliferation Indexmentioning
confidence: 99%